The impact of chronic intermittent hypoxia on enzymatic activity in memory-associated brain regions of male and female rats - Steve Mabry; Jessica L. Bradshaw; Jennifer J. Gardner; E. Nicole Wilson; Janak Sunuwar; Hannah Yeung; Sharad Shrestha; J. Thomas Cunningham; Rebecca L. Cunningham (Biology of Sex Differences)
Abstract Background Obstructive sleep apnea (OSA) is an intermittent hypoxia disorder associated with cognitive dysfunction, including learning and memory impairments. There is evidence that alterations in protease activity and neuronal activation are associated with cognitive dysfunction, are dependent on sex, and may be brain region-specific. However, the mechanisms mediating OSA-induced cognitive impairments are unclear. Therefore, we used a rat model of OSA, chronic intermittent hypoxia (CIH) to investigate protease activity (e.g., calpain and caspase-3) on spectrin, a cytoskeletal protein associated with neurotransmitter release, and neuronal activation (early growth response protein 1, EGR-1) in brain regions associated with learning and memory. Methods Male and female Sprague Dawley rats were exposed to CIH or room air (normoxic) for 14 days. We quantified protease activity and cleaved spectrin products, along with EGR-1 protein expression in hippocampal subregions (CA1, CA3), cortical regions [entorhinal cortex (ETC), retrosplenial cortex (RSC), cerebellar cortex (CC)], and subcortical regions [raphe nucleus (RN), locus coeruleus (LC)] associated with learning and memory. Within each group, Pearson correlations of calpain activity, caspase-3 activity, and EGR-1 expression were performed between brain regions. Sex differences within normoxic and CIH correlations were examined. Results CIH dysregulated calpain activity in male ETC, and female CA1 and RSC. CIH dysregulated caspase-3 activity in male RN, and female CA1 and RSC. CIH decreased calpain and caspase-3 cleavage products in male ETC. CIH decreased calpain-cleaved spectrin in male RSC but increased these products in female RSC. EGR-1 expression was decreased in male and female RN. Correlational analysis revealed CIH increased excitatory connections in males and increased inhibitory connections in females. EGR-1 expression in males shifted from negative to positive correlations. Conclusions Overall, these data indicate CIH dysregulates protease activity and impairs neuronal function in a brain region- and sex-dependent manner. This indicates that males and females exhibit sex-specific vulnerabilities to mild OSA. These findings concur with our previous behavioral studies that demonstrated memory impairment in CIH-exposed rats.